1974
DOI: 10.1149/1.2401926
|View full text |Cite
|
Sign up to set email alerts
|

Native Oxide Mask for Zinc Diffusion in Gallium Arsenide

Abstract: This paper reports the first use of an amorphous native oxide on gallium arsenide to mask against zinc diffusion. Anodic oxides were grown at low temperature (≤100°C), and stripes were defined in this oxide using standard photolithographic processing. These samples were diffused, after an appropriate annealing cycle, in a closed system using a zinc source ( Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
2

Year Published

1974
1974
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
4
2
Order By: Relevance
“…The zinc diffused through all of the anodic oxides we examined in this study. This is somewhat contrary to the results of Spitzer et al 7 who found that when the anodic oxides they employed were annealed at 600~ for 30 rain, only a 1300 A thick oxide was required to mask against a 3300 /k zinc diffusion. However, it should be pointed out their oxides were grown in an H202-H3PO4 electrolyte, their annealing was carried out in nitrogen, and their diffusion was performed with a 5/50/45-Ga/As/Zn source in a closed tube system.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The zinc diffused through all of the anodic oxides we examined in this study. This is somewhat contrary to the results of Spitzer et al 7 who found that when the anodic oxides they employed were annealed at 600~ for 30 rain, only a 1300 A thick oxide was required to mask against a 3300 /k zinc diffusion. However, it should be pointed out their oxides were grown in an H202-H3PO4 electrolyte, their annealing was carried out in nitrogen, and their diffusion was performed with a 5/50/45-Ga/As/Zn source in a closed tube system.…”
Section: Resultscontrasting
confidence: 62%
“…Two basic assumptions in the SI model are that the interstitial concentration is much smaller than the substitutional concentration but the interstitial diffusion coefficient is much greater than the substitutional diffusion coefficient. That is C, << C~ [7] Di >> D~ [8] Therefore Eq. 6 reduces to ac~ ac~ a F D aCi l a~+~}-=~-xL ~-j [9] Because vacancies are being consumed in the SI process, a continuity equation for vacancies is required as well.…”
Section: Resultsmentioning
confidence: 98%
“…An experiment is now in progress to explore these possibilities. A nother class, diffused junction devices, can be optimized using well-con.trolled selective area diffusion (13) along with a diffusion damage buffer (13) as a result of the anodically grown oxides. The sectioning technique provides a fabrication technology for yet another class, mesa or quasi-planar.…”
Section: Device Applicationmentioning
confidence: 99%
“…It has been found that this native oxide acts as a diffusion mask against Zn (13). It is also a barrier against moisture and may act as a barrier to many different atomic species.…”
Section: Device Applicationmentioning
confidence: 99%
“…The growth of native oxides on GaAs and GaP by galvanic and anodic techniques (1-4) using 30% aqueous solutions of H202 as the electrolyte has been shown to be a useful new technology for passivation of semiconductor device surfaces (5,6), as a diffusion mask (7), and for selective area etching (2). The use of a buffered aqueous solution for the growth of an anodic oxide on GaP has recently been described (8).…”
mentioning
confidence: 99%